A Comparative Study of Urban and Rural Youths’ Exposure to Violence in TV Programmes and Susceptibility to Violent Behaviour - Azubuike, Chieme; Ikoro, Nwokezi John (Mediterranean Journal of Social Sciences, 2020)
Television as an agent of education and dissemination of information has touched lives in diverse aspects, especially in education, entertainment and enlightenment. However, even though it parades these positive attributes, it has also encouraged negative attributes to the audience, especially the youths. Youths are susceptible to violence arising from watching TV. Then, the question is who are the most hit by this anomaly - the urban or the rural youth? This is the main thrust of this study. To unravel answers to this question, this study used the survey method where the use of questionnaire was employed. The findings show that the urban youths are more vulnerable to violence due to TV viewing. We therefore, recommend that the parents should guard their children on what to watch; friends to keep. Above all, agencies of government should intensify efforts at making sure that guidelines to dishing out films are adhered to.